Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1038/ng1695
|View full text |Cite
|
Sign up to set email alerts
|

Common deletions and SNPs are in linkage disequilibrium in the human genome

Abstract: Humans show great variation in phenotypic traits such as height, eye color and susceptibility to disease. Genomic DNA sequence differences among individuals are responsible for the inherited components of these complex traits. Reports suggest that intermediate and large-scale DNA copy number and structural variations are prevalent enough to be an important source of genetic variation between individuals. Because association studies to identify genomic loci associated with particular phenotypic traits have focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
282
3
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(302 citation statements)
references
References 27 publications
12
282
3
4
Order By: Relevance
“…However, it is important to determine whether CNVs are in LD with common SNPs, and thus if CNV could be assessed indirectly in SNP-based studies. Regarding this question, although it has been shown that small indels and surrounding SNPs are in LD in the human genome, 30 Redon et al 4 found that diploid copy number of multi-allelic CNVs is poorly predicted by neighboring SNPs. Interestingly, among the populations included in this study the L1/L2 variants (located inside the CNV) have a high correlation with the CCL4L copy number, and, therefore, these variants could be used as a proxy of CCL4L copies of a given population.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to determine whether CNVs are in LD with common SNPs, and thus if CNV could be assessed indirectly in SNP-based studies. Regarding this question, although it has been shown that small indels and surrounding SNPs are in LD in the human genome, 30 Redon et al 4 found that diploid copy number of multi-allelic CNVs is poorly predicted by neighboring SNPs. Interestingly, among the populations included in this study the L1/L2 variants (located inside the CNV) have a high correlation with the CCL4L copy number, and, therefore, these variants could be used as a proxy of CCL4L copies of a given population.…”
Section: Discussionmentioning
confidence: 99%
“…As common indels and SNP variants were previously found to have similar LD profiles [26,31], we predicted that low frequency indels and SNPs would also be similar. We found indel-SNP LD was primarily with frequency matched SNPs - that is, low frequency indels were found to be in LD with low frequency SNPs but not common SNPs (Figure 2b).…”
Section: Resultsmentioning
confidence: 98%
“…Although SNPs and indels arise by different mechanisms in DNA replication or repair, previous studies using only common indels and SNP variants found that these polymorphisms had similar LD profiles, thus implying a shared evolutionary history [27,31]. Using the larger dataset provided by 1000G that includes both common and low frequency variants, we compared the LD properties between pairwise indel-SNP and SNP-SNP.…”
Section: Resultsmentioning
confidence: 99%
“…Current genomic technologies have the capacity to examine millions of single nucleotide polymorphisms (SNPs) and acquired mutations using relatively little starting material, 77,78 and these assays have already been found to be extremely useful for identifying nucleotide changes, uniparental disomy (UDP), and loss of heterogeneity (LOH) in both normal and diseased states. 79 As this technology evolves, arraybased SNP and comparative genomic hybridization platforms will enable researcher to study the genetic variability in hematopoietic cells with increasing precision and genomic coverage.…”
Section: Table 1 To Be Inserted Here Methods To Examine the Regulatormentioning
confidence: 99%